Isolasi dan Karakterisasi Mikrob Pendegradasi Senyawa Nitril - Ahmad Thontowi; Bambang Sunarko (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Biotransformation of nitrile compound using microbe represents the best way in eliminating toxicity. Besides, microbes and enzymes of nitriles degradation can be used in synthesis of various chemical compounds with a high economic value. The purpose of this research is to obtain microbial potential for nitriles degradation, to obtain information of physiological of chosen microbe and the characteristic of its enzyme. We have conducted are isolation and selection of microbial nitriles degradation, perception of growth pattern, determination of influence various and concentration of nitriles on microbial growth, determination of enzymes specificity and inductivity, and determination of optimum pH and temperature. The result of microbial isolation from various sources of waste obtained by 12 isolates at acetonitrile, 18 isolates at benzonitrile, 8 isolates at adiponitrile, 1 isolate at lactonitrile, and 1 isolate at ß- aminopropionitrile. GLB5 isolate was selected from 46 isolates, because this isolate can grow at some tested nitriles. The best growth of GLB5 isolate in acetonitrile 360 mM, benzonitrile 30 mM, 3-sianopiridin 15 mM, and ß- aminopropionitrile 140 mM. The growth of GLB5 isolate in acetonitrile 360 mM were experienced a lag phase during 8 hours, and an exponential phase during 40 hours. Time of cell doubling during 7 hours and 42 minutes, and specific growth rate (µ) equal to 0,09 h-1. The character of nitriles degradation enzymes from GLB5 whole cell was inductive, with optimum activity at pH and temperature equal to 7.2 and 40oC.